Pengaruh Keterlibatan Ayah Terhadap Kematangan Emosi Pada Siswa Di SMAN 1 Tambun Utara - Mawadah, Aulya Zahra; Abdillah, Rijal (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Father involvement is an important role in children's lives, one of which is for the growth and development of emotional maturity. When father role involvement is limited, children may look to other adults, peers, or the media to serve as good role models in life. On the other hand, some students at school may face delayed adulthood due to factors such as a lack of father involvement in their lives. Factors such as these can affect their sense of responsibility and emotional maturity as they experience growing up and later socialize with society directly. Likewise, emotional maturity of adolescents can be stabilized if the role of a father figure can participate in the lives of adolescents. This study aims to determine the effect of father's involvement on emotional maturity in students at SMAN 1 Tambun Utara and uses 298 respondents as research objects consisting of 10th grade and 11th grade students. Based on the normality test obtained, namely 0.200, where p> 0.05 means the data is normally distributed, while for the linearity test, the result is 0.754 which can be said that it is known that the two variables have a positive relationship direction. As for the regression test, the significance value is 0.00 which is <0.05, it can be said that father's involvement has a significant influence on emotional maturity in students at SMAN 1 Tambun Utara.